Enhanced conditioned eyeblink response acquisition and proactive interference in anxiety vulnerable individuals - Holloway, Jacqueline L. (Frontiers Media S.A., 2012)
In classical conditioning, proactive interference may arise from experience with the conditioned stimulus (CS), the unconditional stimulus (US), or both, prior to their paired presentations. Interest in the application of proactive interference has extended to clinical populations as either a risk factor for disorders or as a secondary sign. Although the current literature is dense with comparisons of stimulus pre-exposure effects in animals, such comparisons are lacking in human subjects. As such, interpretation of proactive interference over studies as well as its generalization and utility in clinical research is limited. The present study was designed to assess eyeblink response acquisition after equal numbers of CS, US, and explicitly unpaired CS and US pre-exposures, as well as to evaluate how anxiety vulnerability might modulate proactive interference. In the current study, anxiety vulnerability was assessed using the State/Trait Anxiety Inventories as well as the adult and retrospective measures of behavioral inhibition (AMBI and RMBI, respectively). Participants were exposed to 1 of 4 possible pre-exposure contingencies: 30 CS, 30 US, 30 CS, and 30 US explicitly unpaired pre-exposures, or Context pre-exposure, immediately prior to standard delay training. Robust proactive interference was evident in all pre-exposure groups relative to Context pre-exposure, independent of anxiety classification, with CR acquisition attenuated at similar rates. In addition, trait anxious individuals were found to have enhanced overall acquisition as well as greater proactive interference relative to non-vulnerable individuals. The findings suggest that anxiety vulnerable individuals learn implicit associations faster, an effect which persists after the introduction of new stimulus contingencies. This effect is not due to enhanced sensitivity to the US. Such differences would have implications for the development of anxiety psychopathology within a learning framework.